Tangkil Village Community Motivation in Sports - Syahrudin, Habib; Nurhayati, Maya; Suryadin, Tatang (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
Community activities that are not fully concerned with sports are the main goal of this writing, because based on observations, there are still many people who are more concerned with work or other activities than exercise. The method used in this research is descriptive quantitative. With a research sample of 100 people, the measurement tool uses a questionnaire and data processing uses percentages. The results of this study are the frequency of respondents participating in sports in the village of Tangkil on the dominant factor influencing motivation is internal as much as 87.90%. while on external factors as much as 12.10%. Thus, it can be concluded that internal factors have an influence on participation in sports. The frequency of respondents on the intrinsic factor was 87.90% while on the extrinsic factor was 12.10%. Thus the conclusion that can be drawn is that intrinsic motivation factors have an influence on participation in sports.